2016
DOI: 10.1111/issj.12122
|View full text |Cite
|
Sign up to set email alerts
|

Between inequality and sectarianism: who destroys generalised trust? The case of Lebanon

Abstract: In 2015, a new wave of protests erupted in Lebanon. These protests were the result of a lengthy period of political instability in the country. The informality of the sectarian political system in Lebanon has reached the point where the country has not had a president for more than two years. The aim of this paper is to examine the influence of institutional conditions on the level of generalised trust in a divided society. The paper conducts a statistical analysis of the Arab Barometer Survey data. The paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…As a result, the increase in operational cost as a result of the fact that bribes and other form of grease payments had to be made was cited as the most important effect of corruption on the business sector (Myint, 2000). However, the study also found that employees failed to understand the way in which even petty corruption contributes to the poor quality of public services and the stability of the political system, effects which have been shown to have significant effects on the ability of Lebanese businesses to survive and thrive (Alijla, 2016;Ghoneim & Ezzat, 2016). In contrast, managers had a much wider view of the negative effects of corruption, showing an awareness of the fact that corruption affects the ability to recruit qualified personnel, the certainty of public contracting, the quality of public infrastructure and the stability of the political system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the increase in operational cost as a result of the fact that bribes and other form of grease payments had to be made was cited as the most important effect of corruption on the business sector (Myint, 2000). However, the study also found that employees failed to understand the way in which even petty corruption contributes to the poor quality of public services and the stability of the political system, effects which have been shown to have significant effects on the ability of Lebanese businesses to survive and thrive (Alijla, 2016;Ghoneim & Ezzat, 2016). In contrast, managers had a much wider view of the negative effects of corruption, showing an awareness of the fact that corruption affects the ability to recruit qualified personnel, the certainty of public contracting, the quality of public infrastructure and the stability of the political system.…”
Section: Discussionmentioning
confidence: 99%
“…The high level of corruption has had a negative impact on the economic development of the country (Ghoneim & Ezzat, 2016), has increased the level of citizen distrust in the public sector leading to a general reluctance to follow norms and regulations (Alijla, 2016) and has been cited as one of the major drivers of emigration especially among younger Lebanese (Pearlman, 2013;Dibeh, Fakih & Marrouch, 2017;. The wide spread of various forms of corruption including bribery, nepotism, favouritism, and patronage is a result of a weak legislative framework, numerous conflicts among the political class, a lack of anti-corruption public institutions, as well as a general low level of awareness of the detrimental effects of corruption (The Lebanese Transparency Association, n.d., Ali, 2021).…”
Section: Corruption In Lebanonmentioning
confidence: 99%
“…Moreover, our data suggest that those with a university education exhibited lower political trust than those with no university education. It is noteworthy that sectarianism is pervasive across Lebanese society, which is generally accentuated during times of hardship, such as the COVID-19 crisis (Alijla 2016). Indeed, different sects have continuously competed since the end of the civil war to promote superiority and gain control over political institutions (Traboulsi 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lebanese society has been politically fragmented since the Civil War which has resulted in high levels of mistrust in the political system and its institutions (Alijla 2016). In the context of COVID-19, this may translate into decreased access to the protective effects of community and government support against depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, political trust is defined as trust (or its absence) in the new regime and its influence on the degree that social trust is nurtured and shared. The convergence of political and social trust during and after unrest has been examined in Lebanon, Northern Iraq, Palestine, and among immigrant communities in Denmark (Alijla, 2016(Alijla, , 2019Nannestad et al, 2014;Rydgren et al, 2013), and this article contributes to the discourse by analysing the development of trust and distrust in the microcosm of the Libyan community in Malta. To do so, the article is concerned with the question, how is social trust negotiated by Libyan refugees once they arrive in Malta?…”
Section: Introductionmentioning
confidence: 99%